Comparative study on the effects of crystalline L-methionine and methionine hydroxy analogue calcium supplementations in the diet of juvenile Pacific white shrimp (Litopenaeus vannamei) - Zheng, Lu; Liu, Yuechong; Zhang, Yanmei; Xu, Bingying; Sagada, Gladstone; Wang, Zhixuan; Chen, Cong; Lang, Xiandong; Zhang, Jiaonan; Shao, Qingjun (Frontiers in Physiology, 2023)
An 8-week feeding trial was conducted to evaluate the effects of L-methionine and methionine hydroxy analogue calcium (MHA-Ca) supplements in low-fishmeal diet on growth performance, hepatopancreas morphology, protein metabolism, anti-oxidative capacity, and immunity of Pacific white shrimp (Litopenaeus vannamei). Four isonitrogenous and isoenergetic diets were designed: PC (203.3 g/kg fishmeal), NC (100 g/kg fishmeal), MET (100 g/kg fishmeal +3 g/kg L-methionine) and MHA-Ca (100 g/kg fishmeal +3 g/kg MHA-Ca). White shrimp (initial body weight 0.23 ± 0.00 g, 50 shrimp per tank) were allocated to 12 tanks and divided among 4 treatments in triplicates. In response to L-methionine and MHA-Ca supplementations, the shrimp exhibited higher weight gain rate (WGR), specific growth rate (SGR), condition factor (CF), and lower hepatosomatic index (HSI) compared to those fed the NC diet (p < 0.05). The WGR and SGR of shrimp fed L-methionine and MHA-Ca showed no difference with those in the PC diet (p > 0.05). Both of L-methionine and MHA-Ca supplementary diets significantly decreased the malondialdehyde (MDA) levels of shrimp when compared with the NC diet (p < 0.05). L-methionine supplementation improved the lysozyme (LZM) activity and total antioxidant capacity (T-AOC) of shrimp, while the MHA-Ca addition elevated the reduced glutathione (GSH) levels in comparison with those fed the NC diet (p < 0.05). Hypertrophied blister cells in hepatocytes were observed in shrimp fed the NC diet, and alleviated with L-methionine and MHA-Ca supplementations. Shrimp fed the MET and MHA-Ca diets had higher mRNA expression levels of target of rapamycin (tor) than those fed the NC diet (p < 0.05). Compared to the NC group, dietary MHA-Ca supplementation upregulated the expression level of cysteine dioxygenase (cdo) (p < 0.05), while L-methionine supplementation had no significant impact (p > 0.05). The expression levels of superoxide dismutase (sod) and glutathione peroxidase (gpx) were significantly upregulated by L-methionine supplemented diet in comparison with those in the NC group (p < 0.05). Overall, the addition of both L-methionine and MHA-Ca elevated the growth performance, facilitated protein synthesis, and ameliorated hepatopancreatic damage induced by plant-protein enriched diet in L. vannamei. L-methionine and MHA-Ca supplements enhanced anti-oxidants differently.